An evaluation of clinical decision support tools for Patient Health Questionnaire-9 administration - Naweid Maten, PharmD; Miranda E. Kroehl, MS, PhD; Danielle F. Loeb, MD, MPH; Shubha Bhat, PharmD, MS; Taylor Ota, PharmD; Sarah J. Billups, PharmD; Lisa M. Schilling, MD, MSPH; Simeon Heckman, MS, RN; Crystal Reingardt, MPH; Katy E. Trinkley, PharmD, PhD (American Association of Psychiatric Pharmacists, 2021)
Introduction: Many health care institutions are working to improve depression screening and management with the use of the Patient Health Questionnaire 9 (PHQ-9). Clinical decision support (CDS) within the EHR is one strategy, but little is known about effective approaches to design or implement such CDS. The purpose of this study is to compare implementation outcomes of two versions of a CDS tool to improve PHQ-9 administration for patients with depression. Methods: This was a retrospective, observational study comparing two versions of a CDS. Version 1 interrupted clinician workflow, and version 2 did not interrupt workflow. Outcomes of interest included reach, adoption, and effectiveness. PHQ-9 administration was determined by chart review. Chi-square tests were used to evaluate associations between PHQ-9 administration with versions 1 and 2. Results: Version 1 resulted in PHQ-9 administration 77 times (15.3% of 504 unique encounters) compared with 49 times (9.8% of 502 unique encounters) with version 2 (P = .011). Discussion: An interruptive CDS tool may be more effective at increasing PHQ-9 administration, but a noninterruptive CDS tool may be preferred to minimize alert fatigue despite a decrease in effectiveness.